Validity and reliability of the volleyball serve accuracy-test - Costa, C. L. A.; Valentini, N. C.; do Nascimento, E. M.; Ugrinowitsch, H. (Journal of Human Sport & Exercise, 2024)
This study aimed to examine the content, face, and sensitive validity, and test-retest reliability of a volleyball overhand serve accuracy-test. Four experts - university professors evaluated the content validity; 50 volleyball coaches, teachers, and athletes were enrolled in the face validity. Thirty-three undergraduate students (18 experienced and 15 novices) participated in the study to assess the test capability to detect different performance levels. The sensitive validity was examined by comparing differences in the serving accuracy among experience levels using the t-test for independent samples. A cluster analysis (hierarchical cluster) was conducted using the between-groups linkage method and the Euclidean quadratic distance measure. The test-retest reliability was analysed using intraclass correlation coefficients and the standard error. Satisfactory results were found for experts` agreement regarding the test`s accuracy and content validity. Face validity was adequate regarding clarity, pertinence, and applicability (78% to 86% of agreement). A high degree of test-retest reliability was observed for both novices (ICC = 0.81) and experienced (ICC = 0.84) participants; experienced group (p = .001) had higher means. The volleyball serve accuracy-test is a viable alternative to assess beginners` performance in a teaching-learning context.